EXISTENTIAL REFLECTION AS DIAGNOSTIC CONSTRUCTION: VERIFICATION OF MAIN PROPERTIES - Repetska, Anzhela (PSYCHOLOGICAL JOURNAL, 2018)
The object of our research is the personal self-determination of students. The subject of the study is existential reflection. The aim of the research is to empirically substantiate the conceptual model of existential reflection, to reveal its place and role in the process of personal self-determination. Existential reflection is the mechanism of structuring and transforming the existential experience of the individual. Existential reflection plays an important role in the work of the mechanism of existential sense formation and semantic dynamics. Existential experience is the object of existential reflection. In the structure of existential experience there are three sources of meaning and three mechanisms of sense formation function, respectively: 1) the motive mechanism is based on the meaning of life; 2) the basis of the dispositional mechanism is the self-relation of the individual; 3) the basis of the attributive mechanism is the − I-concept as a set of qualities and characteristics of the individual. The contribution of each source was studied by us with the help of using the corresponding adequate psychodiagnostic techniques: Psychosemantic diagnosis of latent motivation (I. L Solomin). Methods of investigating the self-relationship (S. R Pantileev). Questionnaire of the meaningful crisis (K. V Karpinsky). Methods for determining the dominant state condition (full version, L. V. Kulikov). In the course of During the empirical verification of the conceptual model of existential reflection, 271 students of different universities, different specialties and courses aged from 17 to 22 years were diagnosed. The result of the existential-reflexive work was evaluated through the features of the structure of existential experience, represented by a semantic space of 15 basic concepts − markers of existences. According to the results of the research, it was revealed that for most of the subjects the process of finding oneself (the process of self-determination) and shaping constructing the result of this process − the readiness for self-realization is not actual for the most of represenatives. Against the backdrop of these processes, the existential work of the individual and its component - existential reflexion − on the whole is has spontaneous and latent in nature generally. Our main thesis: existential sense formation, sense-awareness and meaning-building play a key role in the process of personal self-determination.